PENGARUH INSTALASI LISTRIK TIDAK STANDAR TERHADAP RESIKO KEBAKARAN RUMAH DI KECAMATAN PARE KABUPATEN KEDIRI - WARDANA, MOCH. KUSUMA (Jurnal Qua Teknika, 2025)
The Pare sub-district had the highest fire incidence rate in Kediri Regency in 2023, with 20% of fire incidents being house fires, and 37.5% of these caused by electrical installations that did not meet the required standards. The community lacks awareness regarding the use of standard electrical installations. This study employed a qualitative approach, using interviews and observations, and analyzed the data through source and method triangulation to ensure the validity of the findings. The results indicated that all houses of respondents who had experienced fires had non-standard electrical installations. The components of the electrical installation, such as cables, junction boxes, and switches, exhibited a high level of non-compliance, with cables being the most problematic component (100% non-compliant), followed by junction boxes (80%) and switches (60%). Cables were the primary contributor to fire incidents, accounting for 80% of cases. Junction boxes and light fittings also contributed to the fires in the respondents' houses, with each accounting for 10%.